Ice hockey injuries among United States high school athletes from 2008/2009-2012/2013 - Matic, G. T.; Sommerfeldt, M. F.; Best, T. M.; Collins, C. L.; Comstock, R. D.; Flanigan, D. C. (The Physician and Sportsmedicine, 2015)
Background. The popularity of ice hockey has grown in recent years and injuries are a concern given the physical nature of the sport. We sought to report the rates, mechanisms, and severity of boys` US high school ice hockey injuries. We hypothesized that body checking would be a major source of injury and that concussions would be common. We also expected to find that competition would have a higher rate of injury than practice. Design. Descriptive epidemiology study. Methods. Boys` US high school ice hockey injury data from 2008/2009 through 2012/2013 academic years were obtained from the National High School Sports-Related Injury Surveillance System, High School Reporting Information Online database. The primary outcome was rate of injury per 10,000 athlete exposures (AEs). Results. Overall, 724 boys ice hockey injuries occurred during 311,817 AEs for an injury rate of 23.2 per 10,000 AEs. Injury rates were significantly higher during competition compared to practice (rate ratio = 7.8, 95% confidence interval: 6.5-9.4). Concussion was the most frequent injury reported at a rate of 6.4 per 10,000 AEs. Body checking was the mechanism of injury in over 46% of injuries. The head/face/neck region (33.8%) and upper arm/shoulder region (20.6%) were the most commonly injured body sites. Just over 6% of injuries resulted in surgical intervention. Conclusion. Injuries among high school ice hockey athletes are common. Increases in the number of high school ice hockey injuries will likely parallel the increase in high school ice hockey participation in the United States.